Mediator-free carbon nanotube yarn biofuel cell. Issue 54 (16th May 2016) - Kwon, Cheong Hoon; Park, Young Bin; Lee, Jae Ah; Choi, Young-Bong; Kim, Hyug-Han; Lima, Márcio D.; Baughman, Ray H.; Kim, Seon Jeong
Abstract : Mediator-free, microsized yarn biofuel cells are made by simple self-assembly. This system can provide power density up to 236 mW cm −2 and an open circuit voltage of 0.61 V. The system maintained 84% of its initial power for 20 days. Abstract : Enzymatic biofuel cells are the most promising energy sources for implanted biomedical devices. However, direct implantation of biofuel cells has been limited by toxicity from metal-based redox mediators, and by a short operation time because of their instability, especially in physiological conditions. Here we introduce a yarn-type enzymatic biofuel cell for direct electron transfer using surface tension induced self-assembly of aligned multi-walled carbon nanotubes. This biofuel cell offers a maximum power density of 236 μW cm −2, and an open circuit voltage of 0.61 V in 30 mM glucose-containing phosphate-buffered saline, without any mediators or chemical cross-linkers. Furthermore, the proposed self-assembled carbon nanotube-based structure provides enhanced stability for biofuel cells: 84% of the initial power output was consistently maintained after 20 days of continuous operation. Our biocompatible, microsized yarn biofuel cell electrode could be applied easily as needle or catheter shapes in various biomedical fields.